Clinico-epidemiological Analysis of Adult Patients With Acute Poisoning - Soltaninejad, Forogh; Beigi, Ghazal; Golshiri, Parastoo; Eizadi-Mood, Nastaran (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Patients with acute poisoning sometimes require hospitalization in the Intensive Care Unit (ICU). The correct admission of these patients has resulted to lower mortality. This study compared the characteristics of adult patients with acute poisoning who were admitted to the poisoning ward and the ICU. We also determined the relevant outcome predictive factors. Methods: This cross-sectional study was conducted on adult acutely poisoned patients who were admitted to the emergency room of Khorshid Hospital affiliated with Isfahan University of Medical Sciences from October 2018 to 2019. The clinico-epidemiological variables and outcomes were compared between adult patients hospitalized in the ward (n=100) and ICU (n=100). Binary logistic regression was used for predicting the outcome factors. Results: The Mean±SE age of the study patients in the ICU and ward were 36.6±1.62 (median: 34) and 34.20±1.19 years, (median: 33, P=0.23), respectively. There was no significant difference between the study groups respecting substance dependence, alcohol and drug abuse, disease history, and the type of exposure (P>0.05). However, self-mutilation, the kind of substance, the vital signs and level of consciousness at admission, and outcomes were significantly different between the research groups (P<0.05). Variables predicting outcomes (complication/death) were as follows: gender (male) (OR: 4.51; 95%CI: 1.51-13.42; P=0.007), the kind of substance (pesticides) (OR: 8.84; 95%CI: 1.78-44.07; P=0.008), time to admission (OR: 1.04; 95%CI: 1.02-1.08; P=0.002), hypotension (OR: 14.88; 95%CI: 3.01-71.58; P=0.001), and the place of hospitalization (ward) (OR: 2.85; 95%CI: 1.23-6.62; P=0.01). Conclusion: The self-mutilation, kind of substance, vital signs, level of consciousness at admission, and outcomes were significantly different between the study patients hospitalized in the ICU, compared to the ward. Gender (male), the kind of substance (pesticides), delayed arrival times, hypotension, and the place of hospitalization (ward) were essential factors for outcome (complication/death) prediction.